Studies on the Constituents and Medicinal Properties of Some Zingiberaceous Species - M.A, Sukari; B.K, Neoh,; N.Y, Rashid; W.N.F.W.A, Jalil; M, Rahmani; N.H, Lajis; G.C.L, Ee,; A.M, Ali (Malaysian Journal of Science, 2005)
Twelve extracts from four Zingiberaceae species (Curcuma xanthorrhiza, Curcuma heyneana, Kaempferia angustifolia and Kaempferia rotunda) have been screened for antimicrobial assay and cytotoxic screening. Curcuma xanthorrhiza showed strong activity in all biological assays. Two cyclohexane diepoxides, crotepoxide and boesenboxide, together with 2'-hydroxy-4,4',6'-trimethoxychaIcone were isolated from the rhizomes of Kaempferia angustifolia. The structure of these compounds were determined by spectroscopic methods such as infrared (IR), nuclear magnetic resonance (¹H, ¹³C and 2D NMR) and gas chromatography - mass spectrometry (GC-MS) and by comparison with the data reported previously.